The problem of compliance of patients in modern medical psychology - Шестопалова, Людмила Федорівна; Кожевнікова, Вікторія Анатоліївна; Бородавко, Оксана Олександрівна (Psychological Counseling and Psychotherapy)
The article reveals the content of the phenomenon of compliance of patients, suggested his structural-functional model based on the basic provisions of the psychological theory of activity and the theory of functional systems. The basic conditions and laws of formation of compliance, as well as its stages (initial, basic and final). It was found that each of the stages of the establishment of compliance is characterized by specific conditions, which play a key role in its development at this stage.